9y-2x=-11

Simple and best practice solution for 9y-2x=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9y-2x=-11 equation:


Simplifying
9y + -2x = -11

Reorder the terms:
-2x + 9y = -11

Solving
-2x + 9y = -11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9y' to each side of the equation.
-2x + 9y + -9y = -11 + -9y

Combine like terms: 9y + -9y = 0
-2x + 0 = -11 + -9y
-2x = -11 + -9y

Divide each side by '-2'.
x = 5.5 + 4.5y

Simplifying
x = 5.5 + 4.5y

See similar equations:

| 3(x+2)=2(3-x) | | 4(m+1)+7(-m+8)=75 | | 6+3x+3=15 | | y(y-7)-6=2 | | 2x+1+x+4= | | p=3t+2w | | 5n+3n=-12 | | -6(-2v+8)=5(-5v+5)+1 | | 2x-120=180 | | 8d^2+2d= | | -15.00+2.00x=-1 | | 3m-2(m-3)=3 | | 24=3x+6y | | 0.34x+5=9 | | 9x-6-3x=30 | | -5(k-8)+7(-5+k)=-3 | | 2x+10+3x=55 | | 2(u+8)=-6(3u-1)+8u | | 5(4v-5)=5v+4 | | 36=-9(-5+1) | | 8g-3(5+2g)=85-3g | | (3x-4)(7x+5)=0 | | 4y+10=180 | | x+32=3x+24 | | -3(8-7n-2)=18 | | 12f-15=12f-15 | | 14+8m=14-3m-5 | | 16m+4x=y | | 10x^2-36x+27=0 | | 3x-2x-4=17 | | 2(x-5)-(3x+6)=-13 | | In(3x)+In(2x)=3 |

Equations solver categories